2019
DOI: 10.1071/wr19006
|View full text |Cite
|
Sign up to set email alerts
|

Captive husbandry and veterinary care of seabirds during the MV Rena oil spill response

Abstract: ContextSeabirds were the most common taxa captured alive as part of the oiled wildlife response to the grounding of the container vessel MV Rena in the Bay of Plenty, New Zealand. AimsTo describe the management of seabirds during the spill response, to outline the common problems encountered and to make recommendations for future responses. MethodsSeabirds were collected from 7 October 2011 to 14 January 2012. They were stabilised and underwent pretreatment, washing and rinsing procedures to remove oil, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…4 During treatment of pododermatitis of little penguins after oil spill, a reported sedation protocol for debridement included butorphanol (4 mg/kg IM) combined with tiletamine and zolazepam (0.05-0.15 mg/kg) or midazolam (0.1-0.5 mg/kg IM). 5 West et al suggested 1.5 mg/kg midazolam administered IM for the sedation of little penguins for radiology. 2 Many sources also advocate the use of mask induction of anaesthesia with a volatile agent mixed in oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 During treatment of pododermatitis of little penguins after oil spill, a reported sedation protocol for debridement included butorphanol (4 mg/kg IM) combined with tiletamine and zolazepam (0.05-0.15 mg/kg) or midazolam (0.1-0.5 mg/kg IM). 5 West et al suggested 1.5 mg/kg midazolam administered IM for the sedation of little penguins for radiology. 2 Many sources also advocate the use of mask induction of anaesthesia with a volatile agent mixed in oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Of the reported anaesthetic protocols for penguins, there is a large variation in methods and drugs used. [2][3][4][5][6][7][8] General anaesthesia (GA) for MRI acquisition necessitates separation between the anaesthetist and the patient during scanning, increasing the anaesthetist's reliance on monitoring equipment rather than direct patient assessment, as well as having an association with a long duration of procedure.This case describes one anaesthetic protocol, highlights potential complications that may be encountered and suggests improvements that should be considered with future cases.…”
mentioning
confidence: 99%
“…The water pollutants in the lake area in the suburbs of a city are mainly phosphorus and nitrogen indicators. Judging from the monitoring results of the four factors of total phosphorus, total nitrogen, transparency and PH value, which are the evaluation indicators of the nutritional status of the lake, the lake water in the suburban lake area of a certain city is still in a state of eutrophication, with the appearance of periodic intensive growth of aquatic plants and peculiar smell in the water body, resulting in the deterioration of the lake water environment quality in the suburban lake area of a city and affecting the landscape of the lake area [34]. In terms of time distribution, the pollution degree in the suburban lake area of a certain city has strong regularity, and it mostly occurs between May and July every year, in terms of spatial distribution, artificial lakeshore areas are the main areas.…”
Section: Characteristics Of Water Environment Pollutionmentioning
confidence: 99%
“…Little penguins ( Eudyptula minor ) fared the best with nearly 80% survival. Poor body condition upon arrival resulted in higher mortality, while degree of oiling had no significant impact on survival (Gartrell et al, 2019). Other researchers documented adverse impacts to birds from oiling and rehabilitation beyond survivorship.…”
Section: Effects Of Microplastic Debrismentioning
confidence: 99%